Identification of mutations in Iranian patients’ DAX-1 gene with X-linked adrenal hypoplasia congenital - Mahdieh Davoodnejad (Egyptian Journal of Medical Human Genetics, 2017)
Objective(s): X-linked adrenal hypoplasia congenital (X-linked AHC) is a rare disorder, characterized by infantile-onset acute primary adrenal insufficiency and hypogonadotropic hypogonadism (HH) at an average age of three weeks and onset in roughly 40% is in childhood. Its cause is an inactivating mutation in the (nuclear receptor subfamily 0, group B, member 1) NR0B1 gene, DSS (dosage sensitive sex)-AHC vital region on the X-gene 1. Subjects and methods: In the present study, the (dosage-sensitive, sex reversal, adrenal hypoplasia congenital, important region on the X-chromosome, gene 1) DAX-1 gene from four Iranian patients with X-linked AHC was analyzed by means of polymerase chain reaction (PCR) and direct sequencing. Results: We identified a polymorphism (Rs6150) which encodes a cysteine (Cys) at position 38, a de novo deletion, c.849-928del79 bp, c.849-856ins, (TGCTGCA) mutation and a missense mutation, Leu262Gln, which encodes a leucine (Leu) for glutamine (Gln) at position 262. Conclusion: Both mentioned mutations are located at crucial and functional region DAX1 protein. They are detected in the C-terminal region of DAX1 protein which is involved by the conserved amino acid chain as well as transcriptional silencing domain. By considering other investigation, mutations in this region probably lead to produce a misfolded protein. Consequently, the misfolded protein would not work influentially in order to inhibit some gene expression. As a result, our findings will expand the variety of DAX1 mutations. On the other hand, it is revealed that these mutations play a key role in the pathogenesis of AHC, thus, recognizing these new mutations will facilitate the patients prognosis producer as well as raising the clinical knowledge about this rare disease.